¿Hay una teoría de la guerra en Freud? (2008)
ABSTRACT: The author pretends to show how Freud, to put his cause in the psychic, turns war into a necessary element not contin-gent. But on the other hand, creates an ethical dimension that falls on every subject in relation to their own possibilities of aggression, violence.